Modelling of a Stilling Basins with Sloping Apron in IBER to Improve Efficiency in High-slope Rivers - Zabaleta, Y. (2022)
This research shows the influence of stilling basin slopes on energy loss in rivers with a high gradient. This study takes as a case San Pedro water intake (Ayacucho, Peru). The main objective is to improve efficiency of stilling basins in rivers with high slope. Five dissipation pools of different slopes were modelled: 0%, 1.52%, 3.04%, 4.56% and 6.08% to propose the optimum pool among these, for the San Pedro intake. Results were validated by means of a Sensitivity Analysis, trough comparison with the results of previous investigation and results of modelling San Pedro river with HEC-RAS and IBER. It was obtained that the steeper the slope of the stilling basin, the higher the specific energy loss, the higher the output rate, the longer the stilling basin. It can be concluded that the 3.04% slope stilling basin is the most appropriate for the 6.08% slope river since the slope variation is not abrupt as in the case of the horizontal one, that is, 30% more energy loss with respect to the horizontal pool and velocity and Froude results similar to the modelling of the San Pedro river.